Effect of Steam Blanching Time and Drying Temperature towards the Characteristics of Chemistry and Sensory of Bamboo “Tabah” Leaf Tea (Gigantochloa nigrociliata BUSE-KURZ) - Purnama, I Nyoman Cahyadi; Kencana, Pande Ketut Diah; Utama, I Made Supartha (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
Bamboo “Tabah” is one of the bamboo variety of which finds only in Bali island. "Tabah" bamboo leaves have the potential to be developed as raw materials for making tea that can produce drinks with various benefits. If utilized optimally, "Tabah" bamboo leaves can be processed as a product that will provide an advantage. This study aims to determine the effect of steam blanching and drying process on the activity ofwater content, pH, total acid, total phenol, and organoleptic " Tabah" bamboo leaf tea. "Tabah" bamboo leaves are treated with steam blanching time with a variation of time, namely for 10 minutes, 15 minutes and 20 minutes. After steam blanching, the "Tabah" bamboo leaves are dried using an oven with variations in the drying temperature of 50°C, 60°C and 70°C. The research method used was an experimental method with a completely randomized design (CRD) factorial pattern consisting of two factors and repeated three times. The first factor is the steam blanching time and the second factor is the drying temperature. The results showed that the best combination of treatments based on the overall acceptance of hedonic tests produced on “Tabah” bamboo leaf tea is the treatment of 15 minutes steam blanching time with a drying temperature of 60°C (W2S2) which produces 7.03% water content for SNI water content 8%, pH value 6.40, total acid value 0.94%, total phenol content 54.95mg/100g , color scoring test 4.47, aroma scoring test 4.87, taste scoring test 4.60 and overall acceptance hedonic test 4,67.